2016
DOI: 10.1248/bpb.b15-00849
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity Effect of <i>Dioscorea oppositifolia</i> Extract in High-Fat Diet-Induced Obese Mice and Its Chemical Characterization

Abstract: Dioscorea oppositifolia is a well-known edible and traditional medicine for the treatment of gastrointestinal diseases. In our previous study, D. oppositifolia exhibited both pancreatic lipase inhibition and an anti-adipogenesis effect in vitro. This study was performed to investigate the anti-obesity effect of D. oppositifolia on high-fat diet-induced obese mice. Female ICR mice were fed a high-fat diet with the 100 mg/ kg of D. oppositifolia n-BuOH extract for 8 weeks. The high-fat diet mice received the 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
3
14
0
1
Order By: Relevance
“…However, the mice fed on HFD along with oral supplementation of DSHT did not demonstrate significant weight gain, indicating the anti-obesity impact of DSHT. A similar kind of impact on HFD-fed mice was also shown by ORL, in keeping with recent reports revealing a potent inhibitory effect of orlistat on body weight gain in HFD-induced obese rats and mice [26, 27]. Furthermore, there was significant reduction in liver weight, intestinal fat and total fat in HFD + DSHT-treated mice compared to HFD-fed animals, suggesting that DSHT effectively attenuated proliferation or differentiation of adipose tissues.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, the mice fed on HFD along with oral supplementation of DSHT did not demonstrate significant weight gain, indicating the anti-obesity impact of DSHT. A similar kind of impact on HFD-fed mice was also shown by ORL, in keeping with recent reports revealing a potent inhibitory effect of orlistat on body weight gain in HFD-induced obese rats and mice [26, 27]. Furthermore, there was significant reduction in liver weight, intestinal fat and total fat in HFD + DSHT-treated mice compared to HFD-fed animals, suggesting that DSHT effectively attenuated proliferation or differentiation of adipose tissues.…”
Section: Discussionsupporting
confidence: 87%
“…Based on these, it is conceivable that DSHT and ORL may improve the homeostasis of lipid parameters in HFD-induced obese state. Recent studies have demonstrated that orlistat treatment results in marked improvements in serum and hepatic lipid profiles including TG, TC, low-density lipoprotein cholesterol, and HDL cholesterol in HFD-induced obese rats or mice [26, 27]. Collectively, our findings indicate that DSHT combats body weight gain, reduces total body fat, regulates the expressions of leptin and adiponectin genes in adipose tissue, and exerts an anti-diabetic effect by maintaining glucose homeostasis.…”
Section: Discussionsupporting
confidence: 53%
“…Previous research from our laboratory and others illustrated that several flavonoids including puerarin, quercetin, hesperetin, epicatechin, apigenin and anthocyanins could reduced serum lipid levels [ 14 , 15 , 24 , 31 ]. Previous reports have revealed different results regarding the change in serum TG, TC and LDL-C levels of ICR mice treated with HFD for eight weeks [ 32 , 33 , 34 ]. Present observations are in agreement with previous demonstrations that HFD increased the levels of TG, TC and LDL-C [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Herbal formulations as the aqueous extract of Dolichos lablab, the aqueous extracts of Penthorum chinense, ethanol extract ofSolidago virgaurea or isolated flavonoid quercetin, for example, were also able to inhibits hepatic lipid accumulation trough the downregulation of mRNA expression of CD36[40][41][42][43]. Several published data related that orlistat in a range of 10-100 mg/kg is able to reduce liver weight, hepatic triglycerides and serum triglycerides/cholesterol in mice fed with high-fat diet[44][45][46]. AERM demonstrated an in vitro anti-lipase activity less potent than orlistat, but an in vitro anti-amylase more potent than acarbose.…”
mentioning
confidence: 99%